Impact of Covid-19 on Adaptive Functioning of Special Need Children: A Qualitative Study - Waqar, Misbah; Saleha Bibi,; Shamaila Mahmud, (JIE, 2025)
The COVID-19 pandemic has led to global public health concerns, prompting governments to close schools and encourage home stays during emergencies to curb the spread of the virus. The COVID-19 pandemic may have negatively impacted sedentary behavior and physical activity in children and adolescents, raising concerns about their physical and mental well-being. The study aimed to investigate the effects of COVID-19 on the adaptive functioning of special children through qualitative data collection through established interview techniques. Parents of children with exceptional needs provided information about their children's adaptive functioning, using interview guidelines formulated with specialist assistance. The study established an inclusion and exclusion criterion, and parents of children with special needs were contacted individually. Interviews were conducted after informed consent, and themes emerged. The current study's sample size was 7. Results showed increased hyperactivity in children with severe needs and intellectual disabilities. Parents report that COVID-19 has negatively impacted their children with special needs, as they are unable to take them outside and the concept of lockdown and social distancing has not been instilled. Maladaptive behavior in these children is predicted by parents' own stress and routine changes. The research reveals that COVID-19 has negatively impacted the adaptive behaviors of children with special needs due to the lack of therapeutic services, social distancing, lockdowns, and parental stress.